Hypoplastic Left Heart Syndrome Palliation: Technical Aspects and Common Pitfalls of the Hybrid Approach. Issue 5 (September 2022) - Akintürk, Hakan; Yörüker, Uygar; Schranz, Dietmar
The Giessen hybrid strategy is used for initial palliation of HLHS and variants when the intent is to pursue further staged palliative reconstruction toward Fontan circulation. It is also used for initial palliation of HLHC and other anomalies with potential for eventual biventricular repair. From June 1998 - October 2021, 197 patients with HLHS and related variants underwent hybrid stage 1. Follow-up is complete (median 8.3 [range 0-23.3] years). Operative mortality for hybrid stage I was 3.6% (7/197); reduced to 2.8% since 2010 (4/141). Interstage mortality was 4.1% (8/197). Operative mortality for comprehensive stage II was 5.8% (10/172), and since 2010 was 1.8% (2/113 patients). Fontan completion has been accomplished in 117 patients, and 33 are still awaiting stage III. Twelve patients underwent heart transplantation. Over 23 years, overall survival is 77.7% and transplant-free survival is 73.6%.